Predictors of Early Infarct Recurrence in Patients With Symptomatic Intracranial Atherosclerotic Disease. Issue 6 (19th April 2021) - Prabhakaran, Shyam; Liebeskind, David S.; Cotsonis, George; Nizam, Azhar; Feldmann, Edward; Sangha, Rajbeer S.; Campo-Bustillo, Iszet; Romano, Jose G.
Abstract : Background and Purpose: While prior studies identified risk factors for recurrent stroke in patients with symptomatic intracranial atherosclerotic disease, few have assessed risk factors for early infarct recurrence. Methods: We performed a post hoc analysis of the MYRIAD study (Mechanisms of Early Recurrence in Intracranial Atherosclerotic Disease) of intracranial atherosclerotic disease patients with recent (<21 days) stroke/transient ischemic attack, 50% to 99% stenosis and who underwent 6- to 8-week magnetic resonance imaging (MRI) per protocol. Infarct recurrence was defined as new infarcts in the territory of the symptomatic artery on brain MRI at 6 to 8 weeks compared to index brain MRI. Qualifying events and clinical and imaging outcomes were centrally ascertained by 2 independent reviewers. We assessed the association between baseline clinical and imaging variables and recurrent infarct in bivariate models and multivariable logistic regression to identify independent predictors of infarct recurrence. Results: Of 105 enrolled patients in MYRIAD, 89 (84.8%) were included in this analysis (mean age, 64±12 years, 54 [60.7%] were male, and 53 [59.6%] were White). The median time from qualifying event to MRI was 51+16 days, on which 22 (24.7%) patients had new or recurrent infarcts. Younger age (57.7 versus 66.0 years; P <0.01), diabetes (32.6% versus 14.6%, P =0.05), index stroke (31.3% versus 4.6%, P =0.01), anterior circulation location of stenosis (29.7% versus 12.0%, P =0.08), number of diffusion-weighted imaging lesions (>1: 40.0%, 1: 26.9% versus 0: 4.4%, P <0.01), and borderzone infarct pattern (63.6% versus 25.0%, P =0.01) on baseline MRI were associated with new or recurrent infarcts. Age (adjusted odds ratio, 0.93 [95% CI, 0.89–0.98], P <0.01) and number of diffusion-weighted imaging lesions (adjusted odds ratio, 3.24 [95% CI, 1.36–7.71], P <0.01) were independently associated with recurrent infarct adjusting for hypertension, diabetes, and stenosis location (anterior versus posterior circulation). Conclusions: An index multi-infarct pattern is associated with early recurrent infarcts, a finding that might be explained by plaque instability and artery-to-artery embolism. Further investigation of plaque vulnerability in intracranial atherosclerotic disease is needed. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02121028.